SİVEREK VE ÇEVRESİ HALK İNANIŞLARININ DİNLER TARİHİ AÇISINDAN DEĞERLENDİRİLMESİ - UĞUR, GÜLİSTAN (Fırat Üniveristesi, 2021)
Giriş kısmında; ilçenin tarihi, coğrafi konumu, sosyal yapısı, eğitim ve ekonomik durumu, isminin kaynağı hakkında bilgiler verilmiştir. Birinci bölümde Siverek ve çevresindeki geçiş dönemleri ile ilgili halk inanışları ve bu inanışların dinler tarihi açısından değerlendirilmesi, ikinci bölümde ise Siverek ve çevresindeki tabiat ile ilgili inanışlar ve ziyaretlerle ilgili inanışlar ve bu inanışların dinler tarihi açısından değerlendirilmesi yapılmıştır. Araştırmada elde edilen bulgular Dinler Tarihi açısından değerlendirilerek yöre halkının inanç ve uygulamalarının tarihi arka planı ortaya konulmaya çalışılmıştır. Çalışmanın verileri kaynak taraması ve saha araştırması teknikleri ile elde edilmiştir. Ulaşılan veriler deskriptif ve fenomenolojik metotlar kullanılarak yazıya geçirilmiştir. Tezimiz bibliyografya ve ekler kısmı ile sona ermiştir. Anahtar kelimeler: Siverek, Doğum, Evlenme, Sünnet, Ölüm, Tabiat ile ilgili inanışlar.

Our thesis work named "The Evaluation of Folk Beliefs in Siverek and Its Environment in terms of History of Religions" consists of an introduction and two parts. In the entrance part; Information about the history, geographical location, social structure, education and economic situation of the district and the source of its name are given. In the first part, folk beliefs about the transition periods in and around Siverek and the evaluation of these beliefs in terms of the history of religions, in the second part, the beliefs about the nature and visits in Siverek and its surroundings, and the evaluation of these beliefs in terms of the history of religions. The findings obtained in the research were evaluated in terms of the History of Religions and the historical background of the beliefs and practices of the local people was tried to be revealed. The data of the study were obtained by literature review and field research techniques. The obtained data were written down using descriptive and phenomenological methods. Our thesis ends with the bibliography and appendices. Keywords: Siverek, Birth, Marriage, Circumcision, Death, Beliefs about Nature.
The evalation of folk beliefs in Siverek and its surroundings in terms of religion
Keywords: Din; Halk Bilimi (Folklor)